2010
DOI: 10.1002/humu.21249
|View full text |Cite
|
Sign up to set email alerts
|

EYS is a major gene for rod-cone dystrophies in France

Abstract: Autosomal-recessive retinitis pigmentosa (arRP) was recently associated with mutations in a novel gene EYS, spanning over 2 Mb, making it the largest known gene expressed in the human eye. The purpose of this study was to establish the prevalence and nature of EYS mutations in a clinically well-characterized cohort of 239 sporadic and arRP French cases. Direct sequencing of EYS was performed in 186 subjects for whom known mutations had previously been excluded by applying microarray technology. We mostly ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 18 publications
(19 reference statements)
3
77
0
Order By: Relevance
“…Our previous study on 100 Japanese arRP patients indicated very likely pathogenic mutations and possible pathogenic mutations in 18% (18/100) and 8% (8/100), respectively, of the study population; these values are higher than those previously reported. [4][5][6][7] Our previous study has shown that 16% of Japanese patients with arRP displayed either the c.4957_4958insA or the c.8868C4A mutation, which accounted for 57% (15 þ 5/35) of the mutated alleles and seem to be frequent among Japanese patients with arRP. 8 However, a detailed haplotype analysis of the EYS gene has not been performed, and therefore, currently, we cannot verify whether each mutation occurred in an ancient common ancestor.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous study on 100 Japanese arRP patients indicated very likely pathogenic mutations and possible pathogenic mutations in 18% (18/100) and 8% (8/100), respectively, of the study population; these values are higher than those previously reported. [4][5][6][7] Our previous study has shown that 16% of Japanese patients with arRP displayed either the c.4957_4958insA or the c.8868C4A mutation, which accounted for 57% (15 þ 5/35) of the mutated alleles and seem to be frequent among Japanese patients with arRP. 8 However, a detailed haplotype analysis of the EYS gene has not been performed, and therefore, currently, we cannot verify whether each mutation occurred in an ancient common ancestor.…”
Section: Discussionmentioning
confidence: 98%
“…2,3 EYS gene mutations, which include primarily truncating and some missense mutations, have been detected in arRP-affected families of different ancestral origin and are reported to account for 5-16% of arRP cases. [4][5][6][7] Recently, we screened all EYS gene exons in 100 unrelated Japanese RP patients and, found EYS gene mutations in at least 20% of the arRP patients (see the Supplementary Table in the Supplementary Material -available online). 8 In the current study, we examined the clinical features of ten unrelated Japanese patients with RP caused by the EYS gene mutation and compared the phenotype of four patients with the homozygous c.4957_4958insA (p.S1653KfsX2) mutation, which is a major causative mutation of RP in Japan, to that of the other RP patients.…”
Section: Introductionmentioning
confidence: 99%
“…24 In F15 (EORD), we identified a heterozygous known frameshift mutation in EYS (c.9368dup, p.Asn3123Lysfs*3). 25 Subsequent Sanger sequencing of exons with a coverage below 20× did not identify a second mutation. As several copy-number variations (CNV) have been described in EYS, 26 multiplex ligation-dependent probe amplification was performed.…”
Section: Combined Ibd Mapping and Wesmentioning
confidence: 99%
“…So far, 32 genes have been implicated in arRP and 3 additional loci have been mapped (http://www.sph.uth.tmc.edu/Retnet). Most of the identified genes accounted for only 1-2% of cases each, besides EYS (MIM# 612424) and USH2A (MIM# 608400), which were found to account for up to 15.9% and up to 23%-of isolated arRP respectively (Abd El-Aziz et al 2008;Audo et al;Bandah-Rozenfeld et al;Barragan et al;Littink et al 2010) and (Rivolta et al 2000;Bernal et al 2003;McGee et al 2010).…”
Section: Introductionmentioning
confidence: 99%